READING BOOKS: AN EFFECTIVE TOOL FOR ENHANCING CRITICAL THINKING SKILLS AMONG ENGLISH LANGUAGE LEARNERS - Rachuri, Raajitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
At most institutions of higher education, educating critical thinking is widely regarded as one of the central goals. Although a book of literature can be seen as a reproduction of our world within a single four-walled classroom, it has the potential to influence young minds and enhance critical analysis skills, particularly through language teachers. This paper emphasizes the importance of using literature as a medium to develop critical thinking competencies in English for Academic Purposes (EAP) learners. Reading encourages cognitive development, fosters critical thinking, and expands problem-solving skills. Literary genres provide learners with unique ideas, complex characters, and plots filled with twists that leave a lasting impression. Students are compelled to think deeply, critically, and analytically while reading, which helps them master certain higher-order thinking skills. They develop inferential skills, make connections between texts, and cultivate the ability to think about, and beyond, what is stated in a text based on evidence. Additionally, reading enhances creativity, imagination, and empathy, teaching students to see things from the perspectives of others and understand different traditions. Since the late 1950s or early 1960s, incorporating bookwork into language learning classrooms has been shown to foster not only language competence but also cognitive and metacognitive skills. Teachers guide students in shared conversations, reflective prompts, and cooperative efforts that require higher-order cognitive processing. This paper advocates for making extensive reading a key feature of English language instruction, highlighting its contributions to critical thinking, knowledge building, and the development of a reading habit that is essential for lifelong learning. Experimental in nature, this study uses a short story as a text to illustrate and explore the potential for critical thinking among English language learners. The research aims to demonstrate the quality of students’ critical thinking by engaging them with a selected short story. In doing so, it seeks to reveal the insights, analyses, and interpretations that learners can produce as they interact with a narrative landscape. Specifically, the research aims to show that using short stories in English language learning encourages students’ critical thinking.